(untitled) (Global Journal of Medical Research, 2022)
Recent terminology explains dental caries through an understanding of factors that interplay in its etiology, however, the focus is still overpowered by the disease at advanced stages. The aims: (1) extending the concept of dental caries, through the Dental Caries Integrated Ecological Hypothesis (DCIEH), to one that includes the complexity of the disease with its conjoint elements during development and progression (2) update cariology terminology. The terms: dental caries corresponds to the disease and dental caries lesion corresponds to the expression of the disease. Dental caries follows a sequence of progressive phases (mild to severe), characterized by microbiome dysbiosis of the dental biofilm, including the disturbance of the metabolic activity of its commensal microbiota, producing and acid-base imbalance. The dysbiosis is determined by the complex relationship of influential factors regulated by biological features, modulated by behavior, and conditioned by the environment. The chronic imbalance leads to oral homeostasis disruption echoed in a dynamic interaction (demineralization-remineralization) that occurs between the tooth surface and the dental biofilm with subsequent mineral loss. An individual dental caries free should imply that the disease is not present. Instead, dental caries lesion free suggests the absence, after thorough evaluation, of a visible clinical expression at any of lesion stages (from non-cavitated to cavitated lesion). This extended concept allows for a broader understanding of the complexity of the disease, and provides a basis for knowledge to develop tailored strategies that may address the existing condition of the disease and its progression.